OPTIMASI SISTEM HIDROTERMIS JAWA-BALI DENGAN MENGGUNAKAN METODE RANDOM UNIT OUTAGE - Liem Ek Bien, Liem Ek Bien; Welly S, Ajeng (Jurnal Teknik Elektro, 2005)
Regarding increasing of load demand every year, it is necessary to provide power in largeammount which directly involved operation cost especially fuel cost. Therefore, to minimizethe fuel cost, should used an optimization technique that is Random Unit Outage, whichresult not only in minimum operation cost but also reliability level of the system. thisoptimization technique is divided into three steps by three methods; Gradien method,Dynamic Programming, and Convolution method. To test method, it is implemented forJawa-Bali hydrothermal power system of PT PLN (PERSERO) P3BKeywords: interkoneksi, outage, biaya energi terputus